The Realization Of Interpersonal Function On The Tenth Grade English Textbook Of Senior High School Students - Sitinjak, Jesica; Sidabutar, Usman; Lestari, Febrika Dwi (Lembaga Riset dan Inovasi Almatani, 2026)
This study analyzes the realization of interpersonal function in the tenth grade English textbook Bahasa Inggris: Work in Progress used in Senior High School under the Merdeka Curriculum. The objectives are to identify how interpersonal function is realized through mood types and to determine the dominant mood type in the textbook. The study applies Halliday’s Systemic Functional Linguistics (SFL), focusing on the interpersonal metafunction and the Mood system, which includes declarative, interrogative, and imperative clauses. A descriptive qualitative design with document analysis was employed. The data were clauses taken from reading texts. A total of 180 clauses were analyzed by identifying mood elements such as Subject, Finite, Predicator, Complement, and Adjunct, and then classified into mood types. The findings show that all three mood types are realized in the textbook, with declarative mood as the most dominant, functioning to present information and explanation. Interrogative mood is used to guide students’ comprehension and encourage interaction, while imperative mood functions to give instructions and direct learning activities. The dominance of declarative mood indicates that the textbook positions the writer as an information provider and students as receivers of knowledge, although the presence of interrogative and imperative clauses still promotes participation. Overall, the textbook supports communicative learning and contributes to the development of students’ communicicative competence through its linguistic choices.